2024
DOI: 10.3389/fendo.2024.1358404
|View full text |Cite
|
Sign up to set email alerts
|

Association between fatigue, peripheral serotonin, and L-carnitine in hypothyroidism and in chronic fatigue syndrome

Tommi Raij,
Kari Raij

Abstract: BackgroundFatigue of unknown origin is a hallmark symptom in chronic fatigue syndrome (CFS) and is also found in 20% of hypothyroidism patients despite appropriate levothyroxine treatment. Here, we suggest that in these disorders, peripheral serotonin levels are low, and elevating them to normal range with L-carnitine is accompanied with reduced fatigue.MethodsWe conducted a retrospective analysis of follow-up clinical data (CFS N=12; hypothyroidism with fatigue N=40) where serum serotonin and fatigue levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…More specific studies have shown that 5-HT is reduced in brain regions implicated in depression, such as the cerebral cortex ( 68 ), hippocampus ( 63 , 69 ), prefrontal cortex ( 63 , 69 ), and dorsal raphe nucleus ( 65 ), in adult rodents with hypothyroidism. Similarly, clinical evidence has demonstrated that patients with acquired hypothyroidism (without L-T 4 treatment) exhibit lower platelet 5-HT concentrations ( 72 ); this deficiency is also observed in serum samples from hypothyroid patients receiving L-T 4 treatment ( 73 ). Additionally, patients with acquired hypothyroidism have reduced central 5-HT activity, as evaluated by the response to dexfenfluramine ( 74 , 75 ).…”
Section: Acquired Hypothyroidism and Depression: Key Points On Mechan...mentioning
confidence: 97%
“…More specific studies have shown that 5-HT is reduced in brain regions implicated in depression, such as the cerebral cortex ( 68 ), hippocampus ( 63 , 69 ), prefrontal cortex ( 63 , 69 ), and dorsal raphe nucleus ( 65 ), in adult rodents with hypothyroidism. Similarly, clinical evidence has demonstrated that patients with acquired hypothyroidism (without L-T 4 treatment) exhibit lower platelet 5-HT concentrations ( 72 ); this deficiency is also observed in serum samples from hypothyroid patients receiving L-T 4 treatment ( 73 ). Additionally, patients with acquired hypothyroidism have reduced central 5-HT activity, as evaluated by the response to dexfenfluramine ( 74 , 75 ).…”
Section: Acquired Hypothyroidism and Depression: Key Points On Mechan...mentioning
confidence: 97%